Literature review on current research in fluid mechanics in maritime & offshore engineering - Koh, Thomas Yi Feng (2017)
In recent years, several of experiments and researches were being carried out within the Maritime and Offshore engineering with the purpose of improving and discover new ways or design to further improve the field as a whole. Researches were conducted in several area within fluid mechanic field such as drag force, acoustic signal as well as clean and renewable energy such as waves and Wind. It is known that fluid mechanic is an area of study the motion of fluid body be it water or air and the effect to its surrounding environment, and since fluid were a major fraction of consideration within maritime and offshore engineering, thus field of fluid mechanic became a major importance to the maritime and Offshore Engineering sector.